Association of Pericyte Loss With Microthrombosis After Subarachnoid Hemorrhage in ApoE-Deficient Mice - Pang, Jinwei; Wu, Yue; Peng, Jianhua; Yang, Ping; Chen, Ligang; Jiang, Yong (Frontiers in Neurology, 2021)
Background: The occurrence of microthrombosis contributes to not only delayed cerebral ischemia (DCI), but also early brain injury (EBI) after SAH. However, the underlying mechanism is not completely investigated. In the current study, we explored the underlying mechanism of microthrombosis in EBI stage after SAH in ApoE-deficient mice. Methods: Experimental SAH was established by the endovascular perforation in ApoE-deficient (KO) and wild-type (WT) mice on a C57BL/6J background. Neurobehavioral, molecular biological and histopathological methods were used to access the relationship between pericytes loss, neurobehavioral performance, brain water content and microthrombosis in EBI after SAH. Results: The results showed that microthrombosis was significantly increased after SAH and peaked at 48h after SAH in WT mice, as evidenced by significant fibrin(ogen) expression increase in western blot analysis and microthrombi number increase in immunohistochemical staining. In addition, increased microthrombi was associated with effective microcirculation perfusion area and EBI severity after SAH. ApoE-deficient mice showed more extensive microthrombosis than WT mice at 48h after SAH, which was associated with more reduction in effective microcirculation perfusion area, and thereby more significant brain edema and neurobehavioral deficits. Additionally, expression of P-Selectin, the major adhesion molecule that promotes microthrombi formation after SAH, was considerably increased in WT mice and increased to a more extent level in ApoE-deficient mice at 48h after SAH. Further study revealed that the pericytes coverage rate was markedly decreased after SAH. Immunohistochemistry staining showed that microthrombi was predominantly located at microvessels where the pericytes coverage is missing. These changes were more frequently observed in ApoE-deficient. Mechanistically, ApoE deficiency caused more extensive CypA-NF-κB-MMP-9 pathway activation than WT mice, thereby leading to more degradation of N-Cadherin, the core tight junction controlling endothelial cells-pericytes coupling, thereafter resulted in more pericytes loss and microthrombosis after SAH. Conclusion: These data suggest that pericytes loss is associated with EBI after SAH through promoting microthrombosis. ApoE-deficiency can lead to more pericytes loss and microthrombosis, which thereafter resulting in more severe EBI. These changes were mediated at least partly by the CypA-NF-κB-MMP-9 signaling pathway-dependent N-Cadherin degradation. Therefore, ApoE-based therapy is maybe a promising strategy for reducing microthrombosis after SAH.